Hubungan Kualitas Tidur dengan Night Eating Syndrome pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado Angkatan 2024 - Raisa Aurelia, Kemala; Hellen Carol Pangemanan, Damajanty; Polii, Hedison (Journal of Comprehensive Science, 2025)
This study explores the relationship between sleep quality and Night Eating Syndrome (NES) among medical students of Sam Ratulangi University, Class of 2024. Among students/young adults, eating behavior disorders are increasingly prevalent, one of which is NES. Such eating habits are linked to lifestyle factors, sleep duration, sleep quality, and physical activity. This research employs a quantitative approach using observational research methods with a cross-sectional design. The sample consists of 70 students who do not consume sleeping pills. Sampling was conducted using Random Sampling techniques. The results of the analysis showed that there was a relationship between sleep quality and night eating syndrome in students of the Faculty of Medicine, Sam Ratulangi University Class of 2024, where the worse the sleep quality, the higher the risk of NES. Using the Fisher Exact of (0.011), indicating a significant relationship between sleep quality and NES among medical students of Sam Ratulangi University, Class of 2024. The conclusion there is a significant relationship between sleep quality and Night Eating Syndrome (NES).